Exploring the Experiences of DNP-Prepared Nurses Enrolled in a DNP-to-PhD Pathway Program. Issue 5 (September 2018) - Sebach, Aaron M.; Chunta, Kristy S.
Abstract : Abstract: The advancement of the doctor of nursing practice (DNP) degree and the need for nurse researchers with a doctor of philosophy (PhD) has led to significant growth in doctoral nursing education. Some DNP graduates have chosen to pursue a second terminal degree. This descriptive study explored the experiences of students completing a DNP-to-PhD pathway program. Data analysis revealed that DNP-to-PhD students desired acceptance in academia. Implications suggest the need for additional pathway programs, clear communication about program outcomes for both degrees, formal teaching preparation for all nurse educators, and collaborative opportunities for DNP- and PhD-prepared faculty.